Creation of a Neovagina by Laparoscopic Modified Vecchietti Technique: Anatomic and Functional Results - Baptista, Eduardo; Carvalho, Giselda; Nobre, Carlos; Dias, Isabel; Torgal, Isabel (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2016)
Purpose To evaluate the anatomic and functional results of a laparoscopic modified Vecchietti technique for the creation of a neovagina in patients with congenital vaginal aplasia.Methods Retrospective study of nine patients with congenital vaginal aplasia submitted to the laparoscopic Vecchietti procedure, in our department, between 2006 and 2013. The anatomical results were evaluated by assessing the length, width and epithelialization of the neovagina at the postoperative visits. The functional outcome was evaluated using the Rosen Female Sexual Function Index (FSFI) questionnaire and comparing the patients' results to those of a control group of 20 healthy women. The statistical analysis was performed using SPSS Statistics version 19.0 (IBM, Armonk, NY, USA), Student t-test, Mann-Whitney U test and Fisher exact test.Results The condition underlying the vaginal aplasia was Mayer-Rokitansky-Küster-Hauser syndrome in eight cases, and androgen insensitivity syndrome in one case. The average preoperative vaginal length was 2.9 cm. At surgery, the mean age of the patients was 22.2 years. The surgery was performed successfully in all patients and no intra or postoperative complications were recorded. At the first postoperative visit (6 to 8 weeks after surgery), the mean vaginal length was 8.1 cm. In all cases, the neovagina was epithelialized and had an appropriate width. The mean FSFI total and single domain scores did not differ significantly from those of the control group: 27.5 vs. 30.6 (total); 4.0 vs. 4.2 (desire); 4.4 vs. 5.2 (arousal); 5.2 vs. 5.3 (lubrication); 4.2 vs. 5.0 (orgasm); 5.3 vs. 5.5 (satisfaction) and 4.4 vs. 5.4 (comfort).Conclusions This modified laparoscopic Vecchietti technique is a simple, safe and effective procedure, which allows patients with congenital vaginal aplasia to have a satisfactory sexual activity, comparable to that of normal controls.
Keywords: laparoscopy; gynecologic surgery; minimally invasive surgery; mayer-rokitansky-küster-hauser syndrome; androgen insensitivity syndrome; sexuality